2018
DOI: 10.1111/tbed.12914
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the expansion of cutaneous leishmaniasis by Leishmania tropica : Possible implications for control programmes

Abstract: Cutaneous leishmaniasis (CL) caused by Leishmania tropica is emerging in new areas, initially as outbreaks and then establishing endemic foci. There is little evidence of the risk factors and effectiveness of existing control measures, what limits our ability to generalize in different epidemiological settings. The disease is described as anthroponotic; however, zoonotic outbreaks have been reported in some countries. Our aim was to identify risk factors in a recently reported endemic focus in Morocco in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Contrary to the urban type, the presence of confounding determinants has allowed ACL to extend into rural areas (Aflatoonian et al, ; Sharifi, Poursmaelian, et al, ). Numerous risk factors have contributed to the emergence of new CL outbreaks in Pakistan (Hussain et al, ,), Syria (Al‐Salem et al, ; Saroufim et al, ), Morocco (Fatima et al, ; Gijón‐Robles et al, ) and Israel (Gandacu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the urban type, the presence of confounding determinants has allowed ACL to extend into rural areas (Aflatoonian et al, ; Sharifi, Poursmaelian, et al, ). Numerous risk factors have contributed to the emergence of new CL outbreaks in Pakistan (Hussain et al, ,), Syria (Al‐Salem et al, ; Saroufim et al, ), Morocco (Fatima et al, ; Gijón‐Robles et al, ) and Israel (Gandacu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…People who are looking after cattle and other animals are usually at higher risk. All these may act as harbour for sand-flies, which has been confirmed by various studies [19] [23]. A study showed that house ceilings made up of old wood might act as shelter for the sand-fly and significant CL cases were observed in such houses [27].…”
Section: Environmental and Behavioural Practicesmentioning
confidence: 68%
“…What they fail to acknowledge is that, if left untreated, lesions may be superinfected and cause extreme disfigurement, with physical, mental, social, and psychological consequences. In many instances, women do not seek medical care during hospital hours due to their housework demands [23].…”
Section: Community Not Seeking Medical Carementioning
confidence: 99%
“…In El Borouj, L. tropica DNA was detected in 5 out of 184 (2.7%) female P. sergenti (Gijón-Robles et al, 2018) in captures made throughout 2014 (4+/72: 5.6% and up to 18,000 parasites/μg DNA; data not shown) and 2015 (1+/112: 0.9%). The five positive L. tropica females belonged to the most prevalent P. sergenti lineage in El Borouj, lineage IV.…”
Section: Discussionmentioning
confidence: 91%
“…The female P. sergenti from El Borouj in which L. tropicaDNA was detected was identified as a lineage IV specimen. In addition, 4 positive females for L. tropica from captures made in 2014 (Gijón-Robles et al, 2018) were also identified as lineage IV.…”
Section: Mitochondrial Lineage Determination By Mtdna Cyt B Pcr-rflpmentioning
confidence: 99%